"Are We Not What We Seem?": Infrapolitical Maneuvers in the Era of College and Career Readiness. (19th April 2020) - Abad, Miguel N.
Abstract : This article explores the ways in which social scaffolding and cultural brokering processes within educational spaces engender ideological tensions among predominantly Latinx youth participants and educators within a college and career readiness organization. Based upon data from an 18‐month ethnography, they engaged in forms of resistance through infrapolitics. Youth and educators simultaneously critiqued and negotiated the contradictions that emerge from engaging with the symbolic demands associated with respectability and citizenship within the United States.